Vitamin D for prevention of sternotomy healing complications: REINFORCE-D trial - Čečrle, Michal; Černý, Dalibor; Sedláčková, Eva; Míková, Barbora; Dudková, Vlasta; Drncová, Eva; Pokusová, Michala; Skalský, Ivo; Tamášová, Jana; Halačová, Milada (Trials, 2020)
BACKGROUND: Most cardiac surgery patients undergo median sternotomy during open heart surgery. Sternotomy healing is an arduous, very complex, and multifactorial process dependent on many independent factors affecting the sternum and the surrounding soft tissues. Complication rates for median sternotomy range from 0.5 to 5%; however, mortality rates from complications are very variable at 7-80%. Low calcidiol concentration below 80 nmol/L results in calcium absorptive impairment and carries a risk of bone loss, which is considered as a risk factor in the sternotomy healing process. The primary objective of this clinical trial is to compare the incidence of all postoperative sternotomy healing complications in two parallel patient groups administered cholecalciferol or placebo. The secondary objectives are focused on general patient recovery process: sternal bone healing grade at the end of the trial, length of hospitalization, number of days spent in the ICU, number of days spent on mechanical lung ventilation, and number of hospital readmissions for sternotomy complications. METHODS: This clinical trial is conducted as monocentric, randomized, double-blind, placebo-controlled, with planned enrollment of 600 patients over 4 years, approximately 300 in the placebo arm and 300 in the treatment arm. Males and females from 18 to 95 years of age who fulfill the indication criteria for undergoing cardiac surgery with median sternotomy can be included in this clinical trial, if they meet the eligibility criteria. DISCUSSION: REINFORCE-D is the first monocentric trial dividing patients into groups based on serum calcidiol levels, and with dosing based on serum calcidiol levels. This trial may help to open up a wider range of postoperative healing issues. TRIAL REGISTRATION: EU Clinical Trials Register, EUDRA CT No: 2016-002606-39 . Registered on September 8, 2016.
Keywords: Wound Healing; Cholecalciferol; Sternotomy; Healing complications; mužské pohlaví; Cardiac Surgical Procedures; Postoperative Complications; hojení ran; Cardiac surgery; Vitamin D; ženské pohlaví; Humans; kardiochirurgické výkony; sternotomie; vitamin D; Randomized clinical trial; Trial design; Female; pooperační komplikace; lidé; Male